Implementasi Budaya Lokal Bali Ngayah sebagai Penguatan Dimensi Gotong Royong Profil Pelajar Pancasila pada Siswa SDN 3 Mengwi - Made Pertiwi Divayani; Dewa Bagus Sanjaya; I Nengah Suastika (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Strengthening the character of mutual cooperation is one of the primary focuses of implementing the Pancasila Student Profile, which can be developed through the utilization of local culture as a contextual learning resource. This study aims to describe the implementation of the Balinese local culture of ngayah as a means of strengthening the mutual cooperation dimension of the Pancasila Student Profile among students at SDN 3 Mengwi. The study employed a qualitative descriptive approach involving the principal, three teachers, and ten students selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the values of ngayah were implemented through school environmental cleaning activities, preparation for school events, collaborative learning, and environmental maintenance. These activities successfully fostered cooperation, social awareness, responsibility, active participation, and a willingness to help others. Teachers played a crucial role as facilitators by integrating local cultural values into the learning process through habituation, role modeling, and collaborative activities. The implementation of the ngayah culture not only supports the preservation of Balinese cultural heritage but also serves as an effective character education strategy for strengthening the mutual cooperation dimension of the Pancasila Student Profile while developing students who are collaborative, caring, and responsible.